Sistema mitocondrial animal (SISMIT): A computing software applied in the molecular analysis of mitochondrial genomes of vertebrates - Scotto, C. (2000)
The present article reports the design of a computing program which analizes at the molecular level the sequences of mitochondrial DNA (mtDNA) of 37 domestic and wild life vertebrates of zoogenetic importance.